2019
DOI: 10.1190/geo2018-0306.1
|View full text |Cite
|
Sign up to set email alerts
|

Elastic model low- to intermediate-wavenumber inversion using reflection traveltime and waveform of multicomponent seismic data

Abstract: Low-, intermediate-, and high-wavenumber components of P- and S-wave velocities jointly influence the elastic wave propagation and scattering in an isotropic medium. By taking advantage of all information in the data, elastic full-waveform inversion (E-FWI) has the potential to recover these model components. However, if the transmitted wave data are insufficient to illuminate the deeper part of the subsurface, we should rely on the solutions using reflection data. To reduce the nonlinearity of waveform invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…As a reformulated version of FWI, reflection waveform inversion (RWI) has the potential to recover the model low-to-intermediate wavenumbers of the subsurface. However, the current understanding of this approach mainly comes from the analyses and applications of the first-order functional derivative (the gradient), for example, Brossier et al (2015); Li and Alkhalifah (2020); Ma and Hale (2013); Xu et al (2012Xu et al ( ), (2019. It has been observed that numerous iterations in the gradient-based RWI workflow are required to converge toward an appropriate background model (Wang et al, 2018;Xu et al, 2019), which makes it computationally demanding for real scale applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a reformulated version of FWI, reflection waveform inversion (RWI) has the potential to recover the model low-to-intermediate wavenumbers of the subsurface. However, the current understanding of this approach mainly comes from the analyses and applications of the first-order functional derivative (the gradient), for example, Brossier et al (2015); Li and Alkhalifah (2020); Ma and Hale (2013); Xu et al (2012Xu et al ( ), (2019. It has been observed that numerous iterations in the gradient-based RWI workflow are required to converge toward an appropriate background model (Wang et al, 2018;Xu et al, 2019), which makes it computationally demanding for real scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…(2015); Li and Alkhalifah (2020); Ma and Hale (2013); Xu et al. (2012), (2019). It has been observed that numerous iterations in the gradient‐based RWI workflow are required to converge toward an appropriate background model (Wang et al., 2018; Wu & Alkhalifah, 2015; Xu et al., 2019), which makes it computationally demanding for real scale applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation